Efektivitas Pengembangan Hasil Pertanian Dalam Peningkatan Pangan Di Kabupaten Pangandaran - Restu Gumilar (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2023)
This study aims to obtain an answer in research on the Effectiveness of Agricultural Product Development in Increasing Food in Pangandaran Regency. This study uses a qualitative method with a case study approach intended to obtain phenomena in the field so as to produce descriptive data in the form of written words. The data collection technique in this study is by using observation, interviews and documentation techniques. The results of this study indicate that the effectiveness of the development of agricultural products in increasing food in Pangandaran Regency has not been effective in its implementation. This is based on the measurement theory put forward by David J. Lawless (Evi Suryani, 2016:) states that, there are three factors or variables that greatly determine the effectiveness of effectiveness, namely: (1) Individual Effectiveness, (2) Group Effectiveness, (3) Organizational Effectiveness. Solving problems that must be done to keep running organizational effectiveness indicators, while continuing to carry out their duties and functions as they should, because within the organization it can run, and later there will be an increase in the Effectiveness of Agricultural Product Development in Food Improvement in Pangandaran Regency.